PERANCANGAN PLTS ATAP GEDUNG PERPUSTAKAAN UNIVERSITAS UDAYANA - Anggiat Situmorang, Marcelinus; Dwi Giriantari, Ida Ayu; Setiawan, I Nyoman (Jurnal SPEKTRUM; Vol 9 No 2 (2022): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2022.v09.i02.p11, 2022)
Solar Rooftop PV is one solution in reducing CO 2 emissions and the increasing consumption of electrical energy. Based on PP No.79 of 2014, Indonesia is committed to utilizing 23% of the total renewable energy of the total by 2025. In the General National Energy Plan (RUEN), in 2025 Indonesia targets the capacity of electrical energy from new and renewable energy of 45 GW of which solar power of 6.5 GW (14%). In this research, we will discuss the design of Solar Rooftop PV in the Udayana University Library building. Based on the helioscope simulation results, at a real angle of 20.6 o and 20.3 o solar modules that can be installed as many as 84 units with a power capacity of 28.1 kWp while at an optimum angle of 14.66 o , as many as 66 solar modules can be installed with power capacity of 22.1 kWp. Based on the results of the HOMER simulation, the configuration between the real angle PV mini-grid and the grid is able to produce energy of 83,253 kWh/year with an emission reduction of 41.764%, while the configuration of the Solar Rooftop PV with the optimum installation angle with the grid is able to produce energy of 79.775 kWh/year with a reduction in emissions of 34.527%. From the results of the HOMER simulation, an economic analysis was carried out with an energy selling price of Rp. 900/kWh. The two Solar Rooftop PV designs are worth investing in where the Solar Rooftop PV design with a real installation angle of 20.6 o and 20.3 o is able to return the initial investment costs in the 17th year while the Solar Rooftop PV design with an optimum installation angle of 14.66 o able to return the investment cost in the 20th year.